Edukasi Perilaku Asertif melalui Permainan Ular Tangga sebagai Upaya Pencegahan Kekerasan Seksual pada Anak: Education on Assertive Behavior through the Snakes and Ladders Game as an Effort to Prevent Sexual Violence in Children - Patalatu, Jonherz Stenlly; Seipattiseun, Morits Gery Yohanes; Budiman, Veren; Side, Yafet; Laratmasse, Astri F.; Tuny, Margaretha Tabita (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Sexual violence can happen anywhere, anytime, and by anyone. In 2021, the Foster children of Children's Development Center (PPA) ID-0319 were confirmed to have been victims of sexual violence. PPA, as a service institution, has provided psychological and legal treatment and assistance to victims and their families by involving professionals. However, PPA needs education related to the prevention of sexual violence. Therefore, the purpose of this activity is to provide children with an understanding of assertive behavior. The method used was a fun learning approach in the form of presentations, questions and answers, and playing together. This activity consists of 40 participants. After presenting the material, participants played a game of Snakes and Ladders. The results of this activity are the improvement of participants' knowledge, as evidenced by their ability to answer questions on the "asek" learning card correctly. Thus, it can be concluded that the assertive behavior of PPA ID-0319 members can be increased through education.